Assessment of prescribing pattern and quality of life of dermatology patients by using dermatology quality life index - Sangeetha, T.; T., Raghu M.; R., Nataraj G.; Kumar, V. Sharath; Krishna, Y. Satya; J., Fibin Johnson; Manikanta, V. Sravan (International Journal of Research in Dermatology, 2017)
Background: The goal of the study was to assess the prescribing pattern, pattern of skin diseases among the patients and to assess the impact of quality of life in various Skin diseases of dermatological patients by using dermatological quality life index (DLQI). The present study aims at improving the patient’s knowledge towards their disease and medication and also to measure the improvement of Quality of life of patients. Methods: A prospective observational study was carried out for a period of six months at Department of Dermatology Basaveshwara Medical College and Hospital, Chitradurga. Results: Total 150 patients are included. 58 was males and 92 were females. The most skin disease is seen in the age group of 21-40 (40.7%). Majorly skin disease are seen in the illiterate people is (62%), (70.7%) married and 15.3% of socio-economic status of the patients. The major skin disease are seen in the study are psoriasis (12.66%), scabies (16.66%), dermatitis (9.33) and followed by urticaria (6.66%), eczema (4.66%), acne (5.33%). Anti-histamines (16.6%), emollients (9.33%), corticosteroids (9.33%), anti puritics (6.66%), kerotolyte (6.66%) are majorly prescribed drugs. The study showed that there was an extremely significant improvement in DLQI of patients in comparison with first visit result and follow up visit. Whose P value is (<0.001) extremely significant. Conclusions: Therefore the pharmacist patient education found to have significant influence on improves the patient knowledge towards their disease and medication which shows the positive impact on quality of life among the patients of skin diseases.